(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objectives: To assess the knowledge, attitude and practice (KAP) of pregnant women about urinary incontinence (UI), identify the prevalence of UI, assess its impact on quality of life (QoL) and identify factors associated with inadequate KAP in relation to UI. Methodology: Observational study carried out from May to November 2019 in the city of Fortaleza, Ceará, Brazil. Two instruments were used for data collection: one for sociodemographic, obstetric and urinary loss assessment and another for KAP assessment on UI. Results: 237 pregnant women participated. The prevalence of UI was 49.3% and a low impact on QoL was observed. Most had knowledge (89.6%) and inadequate practice both to prevent (89.2%) and to treat (78.8%). Low percentages of correct answers were identified related to knowledge about risk factors (46.8%), prevention (43.8%) and treatment of UI (42.8%). Despite this, the attitude was considered adequate for most women (98.5%). Absence of guidance on preparation of the perineum for childbirth during prenatal care (p = 0.019), low education (p < 0.001), milder cases of UI (p = 0.027) and high-risk pregnancy (p = 0.004) were associated with inappropriate practice. Conclusions: knowledge about the causes, prevention and treatment of UI is insufficient and interferes with the management of this condition.